Actin Dependence of Polarized Receptor Recycling in Madin-Darby Canine Kidney Cell Endosomes - Sheff, David R. (American Society for Cell Biology, 2002)
Mammalian epithelial cell plasma membrane domains are separated by junctional complexes supported by actin. The extent to which actin acts elsewhere to maintain cell polarity remains poorly understood. Using latrunculin B (Lat B) to depolymerize actin filaments, several basolateral plasma membrane proteins were found to lose their polarized distribution. This loss of polarity did not reflect lateral diffusion through junctional complexes because a low-density lipoprotein receptor mutant lacking a functional endocytosis signal remained basolateral after Lat B treatment. Furthermore, Lat B treatment did not facilitate membrane diffusion across the tight junction as observed with ethylenediaminetetraacetic acid or dimethyl sulfoxide treatment. Detailed analysis of transferrin recycling confirmed Lat B depolarized recycling of transferrin from endosomes to the basolateral surface. Kinetic analysis suggested sorting was compromised at both basolateral early endosomes and perinuclear recycling endosomes. Despite loss of function, these two endosome populations remained distinct from each other and from early endosomes labeled by apically internalized ligand. Furthermore, apical and basolateral early endosomes were functionally distinct populations that directed traffic to a single common recycling endosomal compartment even after Lat B treatment. Thus, filamentous actin may help to guide receptor traffic from endosomes to the basolateral plasma membrane.